Marital compatibility among female teachers in Hail City - Al-Hamdhawi, Alaa Falah Fraieh (Journal of Educational and Psychological Sciences, 2025)
This study aimed to measure the level of marital compatibility among female teachers in Hail city from their own perspective. In addition, it revealed the nature of differences among female teachers in marital compatibility according to variables (number of children, duration of marriage, residence, husband's job status, husband's educational qualification, average monthly family income). The study followed the descriptive survey method. The sample consisted of (522) married female teachers. The researcher applied the marital compatibility scale she prepared, which consists of five main axes: (psychological compatibility, intellectual compatibility, emotional compatibility, economic compatibility, and social compatibility). The results of the study revealed that married female teachers enjoy a high percentage of marital compatibility with their husbands (73.70%). Social compatibility scored the highest at (75.24%), while economic compatibility scored the lowest at (72.72%). The study also revealed no statistically significant differences in the responses of the female teachers regarding the level of marital compatibility according to the variables (duration of marriage, number of children, residence, husband's job status, husband's educational qualification, and average monthly family income). Based on the results, the study made several recommendations, including: establishing family counseling centers in schools to provide awareness-raising advice to female teachers, and strengthening family counseling programs to achieve greater marital stability.
Keywords: Marital compatibility; female teachers; Hail City